2011
DOI: 10.1097/scs.0b013e318231e1f3
|View full text |Cite
|
Sign up to set email alerts
|

Myiasis in Palate by Cochliomyia hominivorax

Abstract: Myiasis is the infestation of tissues and organs of animals and humans caused by the larvae of certain dipteran flies. It is more common in undeveloped and tropical countries and usually affects elderly patients, persons who are sick, and patients with mental illness. Oral myiasis is a rare pathologic condition and a risk to the patient's life because of its great destructive potential. Therefore, appropriate treatment is necessary. This article aimed to report a case of myiasis caused by Cochliomyia hominivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…Although this is not a lethal disorder, in older adults, the systemic status is essential for a good prognosis. This case and other similar studies showed successful treatment . However, some cases in older adults with immunocompromised status (anemia, dehydration, low weight), stroke, tube feeding, cancer lesions, or trauma reported the patients died, as a result of these secondary causes, i.e., pneumonia, respiratory failure, and sepsis …”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Although this is not a lethal disorder, in older adults, the systemic status is essential for a good prognosis. This case and other similar studies showed successful treatment . However, some cases in older adults with immunocompromised status (anemia, dehydration, low weight), stroke, tube feeding, cancer lesions, or trauma reported the patients died, as a result of these secondary causes, i.e., pneumonia, respiratory failure, and sepsis …”
Section: Discussionsupporting
confidence: 61%
“…Among 70 papers found in the search, only 26 articles fulfilled the inclusion criteria, total 35 cases (62.9% male, mean age = 76.2 years, ranging from 60 to 97 years), and this study . Three of these articles were not included in the databases searched .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemicals, such as sulphuric ether, olive oil, chloroform, turpentine oil, nitrofurazone, and gentian violet can used to encourage the larvae to exit the mouth through induction of tissue hypoxia . Oral and subcutaneous ivermectin have successfully been used to treat oral myiasis, either alone or in combination with surgical debridement . Ivermectin is a semisynthetic agent from the family of macrolids, synthesized from natural substances, such as avermectin (obtained from actinomycetes).…”
Section: Managementmentioning
confidence: 99%
“…The identification of causative species can be challenging, because of the complex morphological features of the larvae that can only be assessed by a trained entomologist. Species that have been reported to cause oral myiasis, however, include Cochliomyia hominivorax, 17,21,[29][30][31][32][33][34][35][36] Oestrus ovis, 37 Wohlfahrtia magnifica, 9,37 Chrysomya bezziana, 16,20,38,39,41 Hypoderma bovis, 42 Cordylobia anthropophaga, 24 Hypoderma tarandi, 27 Calliphora vicina, 43 Musca nebulo, 38 Musca domesticus, 44 and Lucilia sericata. 51…”
Section: Diagnosismentioning
confidence: 99%